Burnout and associated factors among nurses working in public hospitals of Harari region and Dire Dawa administration, eastern Ethiopia. A cross sectional study. - Deribe Bekele Dechasa (Public Library of Science (PLoS), 2021)
Background Burnout is a syndrome of emotional exhaustion, low personal accomplishment and depersonalization experienced by a health professional and it is more common in nurses due to high workload and job stress that is mostly caused by working proximity to patients and taking care of them. Burnout compromises the provision of quality health care. Despite this, there is no information in Ethiopia on burnout among nurses in study area. Objectives To determine the magnitude of burnout and associated factors among nurses working in public hospitals of Harari regional state and Dire Dawa administration, eastern Ethiopia, February 1-29, 2020. Methods Institutional based quantitative cross-sectional study was employed from February 1-29 among 412 randomly selected nurses who have been working in hospitals for the last 6 months. Simple random sampling method was employed and data was collected by self-administered, standardized, reliable and valid, questionnaire (Maslachs Burnout Inventory- Human Services Survey). Data was entered into EpiData Version 3.1 and exported to statistical package for social science version 20 for analysis. All covariate with P-value less than 0.25 in bivariable analysis were candidate for multivariable analysis. Level of statistical significance was declared at p-value < 0.05. Results Among 412 nurses taking part in this study, 183(44.4%) of nurses with 95% CI, had experienced burnout. Married marital status [AOR:2.3,95%CI:(1.2-4.3)], poor current health status [AOR:4.8, 95% CI:(1.1-21.4)] and fair current health status [AOR:12, 95% CI:(4.5-32)], working greater than eight hour per-day[AOR:0.52, 95%CI:(0.29-0.92)], intention to leave a job [AOR:0.48,95%CI:(0.2-0.88), being working in emergency room [AOR:0.3,95%CI:(0.1-0.98)] and using a different medication related to work related health problems were factors associated with nurses' burnout. Conclusion The nurses' burnout in this study is high and it is attributed by marriage, perceiving health status as poor and fair, whereas, having the intention to leave job, being working in emergency room and using a medication in relation to work related health problems reduced risk of developing burnout. So, the concerned bodies should provide trainings which focus on stress copying mechanisms and assertiveness program.